Hypothermia for newborns with hypoxic-ischemic encephalopathy - Lemyre, Brigitte (Paediatr Child Health, 2018)
Therapeutic hypothermia is a standard of care for infants ≥36 weeks gestational age (GA) with moderate-to-severe hypoxic-ischemic encephalopathy. Because some studies included infants born at 35 weeks GA, hypothermia should be considered if they meet other criteria. Cooling for infants <35 weeks GA is not recommended. Passive cooling should be started promptly in community centres, in consultation with a tertiary care centre neonatologist, while closely monitoring the infant’s temperature. Best evidence suggests that maintaining core body temperature between 33°C and 34°C for 72 hours, followed by a period of rewarming of 6 to 12 hours, is optimal. Antiepileptic medications should be used when clinical or electrographic seizures are present. Maintaining serum electrolytes and glucose within normal ranges, and avoiding hypo- or hypercarbia and hyperoxia, are important adjunct treatments. A brain magnetic resonance image (MRI) is advised shortly after rewarming and, in cases where earlier findings do not match the clinical picture, a repeat MRI after 10 days of life is suggested. Multidisciplinary neurodevelopmental follow-up is recommended.